Photocatalytic degradation of NOx and ethanol in the gas phase by spray dried Ce-TiO2. Issue 6 (December 2021) - Khan, Hayat; Gar Alalm, Mohamed; Lalonde-Lavoie, Marc; Ordonez, Marcela Frias; Sartirana, Marta; Giordana, Alessia; Cerrato, Giuseppina; Bianchi, Claudia L.; Boffito, Daria Camilla
Abstract: We synthesized Ce doped TiO2 (Cex -T) and tested it in the photocatalytic degradation of NOx and ethanol under visible light. Pristine TiO2 (T) and different dopant ratios of Ce-TiO2 (Cex -T; x = 0–1.0 wt%) were prepared by a water-based sol-gel method followed by spray drying. The successful doping of Ce in the lattice structure of TiO2 was confirmed by several characterizations such as X-ray diffraction (XRD), energy dispersive X-ray (EDX), Fourier transform infrared (FTIR), and Raman spectroscopy. All the prepared catalysts grew as spherical grains with a polycrystalline anatase phase. Ce0.8 T revealed the lowest bandgap among all the prepared catalysts (2.8 eV) compared to 3.2 eV for T. The highest degradation of NOx and ethanol was attained by Ce0.8 T (26 ± 1% and 23 ± 1%), which was 2.8 and 1.5 times the degradation by T, Furthermore, we proposed the photocatalytic degradation mechanism by the reactive oxidant species (ROS). Graphical Abstract: ga1 Highlights: We synthesized Ce doped TiO2 (Cex T; x = 0–1.0 wt%). Only the anatase phase was detected in TiO2 . Ce 3+ /Ce 4+, Ti 3+ sand O2 vacancies were detected. Ce0.8 T degraded 26 ± 1% and 23 ± 1% of NOx and ethanol under visible light. Ce0.8 T was 2.8 and 1.5 times more active than T.